Analisis Kebutuhan Tenaga Kerja Rekam Medis (RM) Bagian Filling dengan Metode WISN di RS Pertamina Pusat - Aisyah Fajri Filani; Mochammad Choirur Roziqin; Feby Erawantini (Politeknik Negeri Jember, 2020)
The hospital is a health care institution that conducts complete individual health services and provide inpatient, outpatient and emergency services. Medical record is a unit to collect data patient, processing data, and reporting data that will be an information about performance of the hospital for making decision. In the implementation, competent officers are needed, so that patient services can be carried out optimally and not be hampered by workload in the medical record unit (Zebua, 2016). Pertamina Central Hospital is a plenary hospital managed by PT Pertamina Bina Medika. In 2014-2016 the visitor of outpatient and inpatient was 1157662 visite. In 2017 to 2018, patient visits increased by 21109 visits or 9%. Based on a preliminary survey, the schedule of filling officer is divided into 3 shifts (morning, afternoon, and night). The filling officer has overload working time of 1.5-2.5 hours. The overload working time can be a cause of work accidents. According to Eko (2016), service activities in medical record unit will run smoothly if human resources are sufficient by human needs, workload determined, and based on the standard. In this research is using WISN (Workload Indicator Staffing Needs) method. WISN is a method used to calculate labor needs based on workload. In this method there are 5 stages, selecting the HR category, calculating available work time, calculating workload standards, calculating leeway factors, and calculating labor requirements.